STATE OF HAEMOCOAGULATION IN PATIENT WITH ATRIAL FIBRILLATION AND INFLUENCE OF CONCOMITANT 2 TYPE DIABETES MELLITUS ON ANTICOAGULATIVE TREATMENT - M. V. Kuzub; O. N. Plenova; Y. V. Kovbasniuk (Bogomolets National Medical University, 2016)
The article presents data on the state hemocoagulation in patients with atrial fibrillation and concomitant type 2 diabetes and show that the progress indicated comorbid diseases accompanied by increased blood clotting on the background of inhibition of fibrinolysis. The presence of concomitant type 2 diabetes entails the appointment of large doses of warfarin to achieve an optimal hypocoagulation blood.